Analisis Semiotik Iklan Rokok Sampoerna A Mild (Studi Semiotik Iklan Rokok Sampoerna A Mild Versi “kita gak enakan dia seenaknya” dalam Media Televisi) - Sonaria, Andari (LANCAH: Jurnal Inovasi dan Tren, 2024)
Semiotics is a science or method for studying signs. Advertisements contain signs that appear and produce the meaning of the message in the advertisement. The aim of this research is to analyze the implied messages in the "we use him as we please" version of the Sampoerna A Mild cigarette advertisement shown on television using Ferdinand de Saussere's semiotic approach. The object of research is the Sampoerna A Mild cigarette advertisement with this version. The research method used is semiotic analysis, namely by analyzing the signs, signifiers and referents contained in the advertisement. The results of the analysis show that there are various implied messages in advertising scenes related to individualistic behavior conveyed implicitly. The cigarette advertisement succeeded in conveying certain messages implicitly through creative strategies for presenting scenes and raising topics that were relevant to society's culture.